The Heart of the Matter: Health Status of Aged Care Clients Receiving Home- and Community-Based Care - Deborah Yarmo-Roberts; Rosanne Laura Freak-Poli; Brad Cooper; Tim Noonan; Just Stolewinder; Christopher M. Reid (Journal of Aging Research)
Objective. To determine the current health status of home based elderly clients receiving government funded aged care packages. Design. Prospective Observational study. Setting. Community based, home care program in Australia. Participants. Community-dwelling older adults receiving aged care packages. Measurements. A comprehensive test battery of physical, mental and social scales were completed including a Caregiver Strain Index where appropriate. Results. 37% of the 334 subjects were male and the mean age was 81±8 years. Physical functioning was low compared to the Australian population. Depression was highly prevalent with 15.9% severely depressed and 38.7% mildly depressed. 26% of clients screened positive for dementia. Relatively good levels of social support were reported, however social networking activity levels were low. Sixty one percent of clients had caregivers, of whom 63.3% had high levels of strain. Strain was higher in caregivers of clients on higher levels of care (78.5% versus 50.6% highly strained). Conclusion. The data suggests that as a group there is a high degree of comorbidity, and depression, dementia and caregiver strain are highly prevalent. The findings may aid administrators and health policy planners in directing resources to key areas impacting on health outcomes in this group.